Last stand of dead men / 8. - Landy, Derek (Skulduggery Pleasant, 2013)
The war between sanctuaries that everyone has been expecting has finally come, with the Supreme Council making a desperate grab for control of a cradle of magic, sparking a brutal war that will turn friend into enemy, and ally to foe. But even as the Dead Men make their final stand for their country and their freedom, there is another war raging, inside Valkyrie Cain herself, and it is much more important. Because if she loses, Darquesse will rise, the world will burn, and everyone she knows and loves will perish.